Report of the Special Group on Targeting Ten Million Employment Opportunities Per Year Over the Tenth Plan Period - Planning Commission (Planning Commission, 2002)
The Special Group on "Targeting Ten Million Employment Opportunities per year over the Tenth Plan Period" has been constituted by the Planning Commission by drawing experts from the Steering Committee on Labour and Employment for the Tenth Plan Constituted by the Planning Commission and co-opting experts and specialists from within the Government and from academics, and practitioners in this area. The Terms of Reference of this Group is Given in Annexure "C" of this Report.
Planning Commission Government of India
Planning Commission Government of India